E-Prescription: Opportunities and Challenges - Jamil, Ahmad Mochtar; Fahrudda, Ansarul; Mundakir, Mundakir; Hartamto, Offia Melda Permata; Absor, Sholihul; Suswojo, Heru; Anas, Muhammad; Rahmah, Laila (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background: The research explores the advancements and implications of e-prescribing systems within modern healthcare.Objective: The primary objective is to assess the growing body of literature, examining global trends, effectiveness, and challenges associated with e-prescribing implementation.Methods: Using a comprehensive literature review methodology, data were sourced from the Scopus database, revealing many publications from 1980 to 2024.Results: A notable increase in scholarly interest was observed, particularly from 2015 to 2024, highlighting e-prescribing as a mature research subject. The results indicate a high concentration of research activity in advanced healthcare systems, contrasting with the limited contribution from developing contexts such as Indonesia.Conclusion: The study identifies that while e-prescribing improves medication safety and efficiency, gaps in understanding its long-term impacts on patient outcomes persist. Additionally, disparities in technology adoption among demographic groups emerge as significant barriers. This research contributes to existing knowledge by underscoring the need for localized studies and international collaboration to enhance e-prescribing practices. Future research directions should focus on evaluating long-term outcomes, improving digital literacy, and assessing training impacts on healthcare professionals.